AB0724 Biomarkers Sensitive to Change in Patients with Systemic Sclerosis – a Systematic Review. (9th June 2015) - Toniolo, M.; Dobrota, R.; Moinzadeh, P.; Ogawa, R.; Furst, D.E.; Denton, C.P.; Khanna, D.; Distler, O.
Abstract : Background: Currently available clinical measures in systemic sclerosis (SSc) are depending on the organ manifestation of interest and have a low sensitivity to change, in particular over shorter observation periods. Biomarkers are more sensitive than traditional measures and have been extensively studied in SSc. However, most biomarker studies focused on cross-sectional analysis, while there is an urgent need for biomarkers that are sensitive to change. Objectives: We conducted a systematic literature review to identify biomarkers which are sensitive to change over time or treatment in patients with SSc. Methods: Both PubMed and Cochrane CENTRAL databases were searched to identify articles pertaining to the field of SSc and biomarkers. Studies were eligible if they were written in English and presented data from human subjects. The search was initially performed on March 18th, 2011 and renewed on March 23rd, 2013. The results were reviewed by two independent scleroderma experts, through a stepwise selection strategy starting from titles, to abstracts and manuscripts. Studies which did not present original research (e.g. reviews, case studies) were excluded. Moreover, only studies reporting changes in biomarkers and clinical endpoints between the baseline and follow-up visits were included in the final analysis. The identified biomarkers were assessed according to OMERACT criteria. Results: The initial search identified 960 unique citations; 721 titles were excluded, leaving 239 abstracts for review; 170 of these did not meet the study criteria. The remaining 69 papers were analyzed full-length and subsequently 15 papers showing longitudinal analysis between biomarkers and clinical endpoints were identified. After filtering according to the OMERACT criteria, several biomarkers sensitive to change over time and/or treatment were identified. Markers of skin fibrosis included E-selectin, Thrombomodulin, Interleukin-1-beta, Interleukin-6. For lung fibrosis, E-selectin, Thrombomodulin, sICAM3, sPECAM-1, KL-6, Surfactant protein D showed sensitivity to change over time or treatment. Markers of vasculopathy were as follows: pulmonary arterial hypertension (sICAM-1, sVCAM-1, sP-selectin, NT-proBNP, MMP-9, IL-12), digital ulcers (sICAM-1, t-PA), Raynaud's (VEGF, bFGF, sVCAM-1, E-selectin, sICAM-1, t-PA, VCAM-1) and pathologic capillaroscopy (IL-6, IL-1β). Conclusions: This is the first systematic analysis in SSc for biomarkers sensitive to change over time or treatment. It provides evidence based data for candidate biomarkers to be used in clinical trials and potentially in clinical practice. Disclosure of Interest: M. Toniolo: None declared, R. Dobrota Grant/research support from: Articulum Fellowship (Pfizer), Actelion, P. Moinzadeh: None declared, R. Ogawa: None declared, D. Furst: None declared, C. Denton: None declared, D. Khanna: None declared, O. Distler Grant/research support from: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation, Consultant for: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation